The effect of (cognitive-behavioral) treatment in reducing psychological stress for female students of the Teachers Preparation Institute - Khader, Batoul (Al-Adab Journal, 2023)
The study aimed to identify the effect of the proposed remedial program in reducing psychological stress among the students of the Institute of Teachers Preparation, while the research hypotheses were the existence of statistically significant differences between the control group and the experimental group in the psychological stress test and in favor of the experimental group. The research sample included (20) female students from the Institute The preparation of the parameters / first stage / were chosen by the method. The research sample was divided into two control and experimental groups with (10) students for each group. The proposed program was applied to the experimental research sample. The researcher chose the psychological stress scale, which aims to reduce stress, anxiety and tension for the students. As for the behavioral treatment program, which It consists of (8) treatment sessions at two sessions per week, which aims to replace negative thoughts with positive ones. The researcher used the (Mann-Whitney) test for small identical samples in statistical treatments. The results of the research proved that the proposed cognitive behavioral treatment program had a clear effect in reducing psychological stress among Students of the Institute of Teachers Preparation, and thus the research hypothesis